ANTARA â€œALAT TULIS ATAU ALAT COBLOSâ€: STUDI KASUS SURAT SUARA TIDAK SAH DALAM PEMILIHAN SERENTAK LANJUTAN 2020 DI KABUPATEN SEMARANG - maskup, maskupmutarlih (Talenta Publisher, 2022)
The purpose of this review is to study the Pattern of Invalid Ballot due to the voterâ€™s incomprehension on the recommendations in the C-Notification Form to bring their own stationary. This descriptive qualitative research uses documentation studies and interviews as the data collection method, it identified that the invalid ballots pattern arises from the use of stationary as the election tool. The use of stationary as the election tool contributes to the significant high number of invalid ballots in the Semarang Regency which reached the total of 33.511 invalid ballots or 5,5% from 608.997 people who exercised their right to vote, in fact in some Voting Places the total number of invalid ballots was more than 10%. It was further revealed that the reason the stationary was used as the election tool, among others was because voters were afraid of getting infected by the virus if the election tools were used interchangeable by other voters. Secondly, the recommendation for voters to bring their own stationary, unconsciously reminded people of the mark ballots in the 2009 Election and due to this, in some Voting Places in the last Semarang Regent 2020 General Election, many stationaries were left behind